New Mass Communication Media and the Identity of Negev Bedouin Arab Youth in Israel: In Conversation with Edward Said - Gribiea, Adnan (Journal of Holy Land and Palestine Studies, 2017)
Mass communication media technologies influence the structuring of reality, consolidation of value systems, and construction of common social denominators, and thus contribute to the formation of personal and national identities. While, as Edward Said has shown, mainstream Western (including Israeli) media have been dominated by Orientalist, anti-Arab/anti-Islamic perspectives, new media technologies have opened up a broad range of media options lying beyond the reach of Western media's hegemonic presentations. This article explores the use of new mass communication media technologies and their association with identity formation in connection with Bedouin Arab high schools in the Negev, Israel. The findings of this research indicate that Negev Bedouin Arab youth developed diversified patterns of mass media consumption. They also show a preference for Arab media sources. Media consumption patterns are related to their national and civic identities. The findings also indicate that Bedouin Arab youth have a stronger Palestinian national identity than Israeli civic identity.